Market Driving to Develop Rabbit Meat Products in Indonesia - Atien Priyanti; Yono Cahyo Raharjo (Indonesian Center for Animal Research and Development, 2012)
Rabbit meat is a nutritional food containing high protein and low cholesterol, fat and sodium. Current research in rabbit production is aimed for developing production strategies to increase the nutritional and economic values of rabbit meat products as functional food. Nowadays, producing rabbit is a popular farming activity in many parts of Indonesia as a small and medium scale operation for food security and cash income. Rabbit farming is to produce meat, skin and hides, fur, organic fertilizers and pet or fancy animals. Consumption of rabbit meat is considered very low, due partly to low meat supply and inavailability of marketing. In some tourist areas, such as Lembang (West Java), Tawangmangu (Central Java), Sarangan and Batu (East Java) rabbit meat is a specific food. Attempt to create and drive rabbit markets will simultaneously increase meat production to fulfill the demand and meet economic scale of farming. Hence, this will give significant impact to the farmers’ welfare. Availability of good quality meat, dissemination and diversification of meat products, production efficiency toward competitive price along with its proper marketing strategy will drive consumers’ preferences to consume more rabbit meat. Market driving needs to be created in order to promote rabbit meat products by establishing food outlets. This program has been developed by a farmers group in Magelang, Central Java. During the period of 2006 – 2007 the food outlets had increased to 5 outlets, and in 2012 become 9 outlets. This market driving will also have an impact on changing orientation of rabbit farming from traditional to a small and medium economic scale that will influence the production efficiency.Key words: Market driving, rabbit production, farmers group association